Fabrication and characterization of B4C and BN refinforced aluminium matrix composites by squeeze casting - Nekouyan, Amin. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
Aluminium matrix composites (AMC) with different ceramic particle reinforcements gained significant attention due to high demand for materials with versatile properties in the industry. In the present work boron carbide (B4C) and boron nitride (BN) ceramics in different volume fractions were used as the reinforcement materials to fabricate Al-B4C and Al-B4C-BN composite materials which then underwent different squeezing pressures. The processes of this study were conducted in two steps. In the first stage, the effect of various B4C contents (3 % , 5 % and 10 % ) under different squeezing pressures (0, 75 and 150 MPa) were studied for tensile strength, hardness characteristics, machinability, density and the microstructure of fabricated samples. In the second stage, Al-B4C-BN hybrid AMC samples were manufactured with constant squeezing pressure (75 MPa) and constant B4C volume fraction of 5 % but with three different BN volume fractions (3 %, 5 % and 10 %). For this purpose, again previously mentioned tests were applied on the samples. Total of 105 samples were manufactured and tested. One of the main challenges in the manufacturing process was low wettability of B4C and BN particles with aluminium melt which was successfully overcome by addition of K2TiF6 flux in the case of B4C and applying high temperatures in the case of BN. The main objectives of this research are first to evaluate the effect of B4C reinforcement and squeeze casting on the properties of AMC. Secondly since it is known that Al-B4C AMC would have low machinability due to the presence of abrasive B4C particles, it is aimed to evaluate how addition of BN particles with lubricating properties can improve this drawback and thirdly to find out what is the optimum composition of AMC to be used in the industry. Also it was finally aimed to evaluate the effect of K2TiF6 on wettability of B4C particles by aluminium melt.
Keywords: Aluminum alloys.